The growth and carcass weight of young Watish Sudan Desert sheep when fed concentrate supplements to berseem (Medicago sativa) grazing - Ahmed, F.A.; Pollott, G.E.; Mohammed, O.M. (1979)
Young Watish lambs grazing berseem grow at 148 and 105 g/day for males & females respectively, over a 20-week period. The provision of various concentrate supplements marginally increased live-weight gains but this practice was not recommended as being of economic value. Hot carcass weight of young Watish lambs was highly related to live-weight at slaughter but killing-out percentage was less so. The practical implications of these results are discussed.